Culture et propagande franquiste dans l’Argentine péroniste - Laurent Bonardi (Amnis)
The end of World War II and the international condemnation of Spain put Franco’s regime in a very delicate situation. However, the Argentinian government of the general Peron appeared as a “life jacket” for the Spanish dictatorship. The government of the Caudillo used this context to develop a very intense propaganda in the Rio de la Plata. Still, to conclude their various propagandist actions, the Spanish representatives in Argentina had to fight against the activities of antifranquist people in exile.